1991
DOI: 10.1128/mcb.11.2.1171
|View full text |Cite
|
Sign up to set email alerts
|

An okadaic acid-sensitive phosphatase negatively controls the cyclin degradation pathway in amphibian eggs.

Abstract: Inhibition of okadaic acid-sensitive phosphatases released the cyclin degradation pathway from its inhibited state in extracts prepared from unfertilized Xenopus eggs arrested at the second meiotic metaphase. It also switched on cyclin protease activity in a permanent fashion in interphase extracts prepared from activated eggs. Even after cdc2 kinase inactivation, microinjection of okadaic acid-treated interphase extracts pushed G2-arrested recipient oocytes into the M phase, suggesting that the phosphatase in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
1

Year Published

1991
1991
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(42 citation statements)
references
References 27 publications
1
40
1
Order By: Relevance
“…Inhibition of phosphatase activity by microcystin or okadaic acid causes spontaneous, Ca 2+ -independent destruction of cyclin B in CSF extract. 33,34 When we reexamined this observation in terms of Emi2, we found that, unlike Ca 2+ -induced CSF release, the cyclin B destruction caused by phosphatase inhibition was not accompanied by Emi2 destruction, suggesting the existence of a kinase-dependent loss of Emi2 function. 20 This could be through direct inactivation of Emi2, or through the APC/C becoming refractory to Emi2's inhibitory activity.…”
Section: Resultsmentioning
confidence: 97%
“…Inhibition of phosphatase activity by microcystin or okadaic acid causes spontaneous, Ca 2+ -independent destruction of cyclin B in CSF extract. 33,34 When we reexamined this observation in terms of Emi2, we found that, unlike Ca 2+ -induced CSF release, the cyclin B destruction caused by phosphatase inhibition was not accompanied by Emi2 destruction, suggesting the existence of a kinase-dependent loss of Emi2 function. 20 This could be through direct inactivation of Emi2, or through the APC/C becoming refractory to Emi2's inhibitory activity.…”
Section: Resultsmentioning
confidence: 97%
“…We reported previously that the cyclin degradation pathway is turned on for only one round in the absence of phospatase inhibitor, and inactivates when endogenous cyclins A and B have been destroyed. In the presence of okadaic acid or microcystin in contrast, the cyclin degradation machinery remains switched on in a permanent fashion (Lorca et al, 1991a).…”
Section: Resultsmentioning
confidence: 99%
“…An okadaic acid/microcystin-sensitive phosphatase has been shown to negatively control the cyclin degradation pathway in eggs and early embryos of both vertebrates and invertebrates (Felix et al, 1990b;Lorca et al, 1991a;Lahav-Baratz et al, 1995). Constitutive activity of this phosphatase is believed to turn o APC Fizzy activity when cyclin B-cdc2 kinase drops below a critical threshold activity.…”
Section: Fizzy Introductionmentioning
confidence: 99%
“…MPF activity depends on the stability of cyclin B . Moreover, OA is known to indirectly activate MPF in Xenopus oocytes and extracts (Goris et al, 1989;Rime et al, 1990;Jessus et al, 1991;Lorca et al, 1991). Therefore, the sensitivity of EDEN-dependent deadenylation to OA could be due, in part, to activation of MPF.…”
Section: Mpf Pathway Does Not Inhibit Eden-dependent Deadenylationmentioning
confidence: 99%